(untitled) (Al-Academy, 2023)
Contemporary art has been widely affected by technology, and ceramics production is no exception. As an ancient art that originates from clay and other humble materials found in the ground, ceramics is considered one of the most adaptable art forms. Once it is realised how flexible ceramics as a material is, it can be easily altered into endless forms and shapes. Therefore, it is vital for ceramics practitioners to find a relationship between this wonderful material and the media of contemporary art, culture and modelling software or technology in general so that they can take their deformable art pieces to a whole new level. Such a relationship is worth investigating. Thus, for the purposes of this research, several ceramic pieces were identified using AutoCAD software to design authentic artworks with a contemporary look and feel. Throughout the research, these artworks will be examined from different perspectives. This will show in detail how art became not only a technical form or design but also a representation of expressive values stemming from diversity and unity. In this paper, the possibility will be discussed of experimenting with modelling software to develop traditional utensils into contemporary ceramic art by applying an advanced method of deconstruction. In addition, this paper will explain how technology is used to improve the quality of clay utilised in the production of art, producing a composite suitable to be formed, modelled, and dismantled in and through modelling software.